PERSEPSI ANGGOTA DPRD KOTA SEMARANG PERIODE TAHUN 2014-2019 TERHADAP PILKADA LANGSUNG - yulika nourmalasari hayuningtyas; SUSILO UTOMO; FITRIYAH . (Journal of Politic and Government Studies, 2016)
This research is done to know perception from the Members of Parliament Semarang Period Year 2014-2019 toward the direct local leader election. Through understanding the knowledge of local democracy, opinions about local democracy, and evaluation of the local democracy. This study used a quantitative approach with quantitative descriptive type. These data were obtained through a questionnaire toward the the population of Semarang City Council Member for the Period of 2014-2019. Respondents were selected by random sampling technique of proportional calculation with total number of 30 respondents. Furthermore, the data analysis was performed by busing SPSS 16.0.          The results of this study showed that the majority of the Members of Parliament of Semarang the year period 2014-2019 approve the implementation of direct elections. One thing that becomes an obstacle in the implementation of direct elections is the practice of money politics that is unavoidable.          Finally, it is hoped that this rsearch result can be a means of evaluation and opinion of Semarang City Council Member the year period 2014-2019 related to perception from the Members of Parliament Semarang Period Year 2014-2019 toward the direct local leader election. Keywords: Perception, Direct Election, Member of Parliament Semarang